INVESTIGATION INTO M-COMMERCE CONSUMERS HEDONIC BROWSING AND THE IMPACT ON URGE TO BUY IMPULSIVELY - Nazirah, Ulyatul; Utami, Sorayanti; Ma’ruf, Jasman J. (Jurnal Ilmiah Teunuleh, 2022)
One way to buy online is through m-commerce. In the discussion of consumer behavior to make a purchase, there are many influences that underlie a person in making purchasing decisions. The theory of motivation has become a reference for many researchers to understand and know the motivation of users and the responses that occur to various stimuli. This research was conducted on consumers who have made purchases using m-commerce in Indonesia. The purpose of this study is to analyze the correlation between interpersonal influence, visual appeal, and portability, with urge to buy impulsively and urge to buy impulsively through hedonic browsing. The data was analyzed using Structural Equation Modelling. The results shows that interpersonal influence has a significant effect on urge to buy impulsively, visual appeal has a significant effect on urge to buy impulsively, portability has a significant effect on the urge to buy impulsively, interpersonal influence has a significant effect on hedonic browsing, visual appeal has a significant effect on hedonic browsing, portability has a significant effect on hedonic browsing, hedonic browsing has a significant effect on the urge to buy impulsively, hedonic browsing mediates the influence of interpersonal influence on urge to buy impulsively, hedonic browsing mediates the effect of visual appeal on urge to buy impulsively, and hedonic browsing mediates the effect of portability on the urge to buy impulsively.